Analysis Of Sharia Laundry Marketing Strategy In Mamuju District: Analisis Strategi Pemasaran Laundry Syariah Di Kabupaten Mamuju - Sibgatullah, Muhammad; Furqan, Furqan; Acha, Hamzar; Kurnia, Kurnia; Febriandika, Nur Rizki (Universitas Muhammadiyah Sidoarjo, 2023)
Awareness of carrying out religious law is escalating daily among the Indonesian people, most of whom are Muslims. This outlook is not only seen in worship that is directly related to God, but it has penetrated into economic activities. This study aims to ascertain the marketing strategy for Sharia Laundry in Mamuju Regency. This exploration employs a phenomenological qualitative approach with in-depth interviews, documentation and observation techniques, then the data are analysed descriptively. The profound results indicate that Sharia Laundry marketing prioritises the sharia washing system, purity, cleanliness, friendliness, close distance, delivery system, promotions on social media and special promos. The primary difference between this sharia laundry enterprise and other laundry services is that before washing, the garments are rinsed using running water to remove impurities. After that, they are put into the washing machine with a one-machine system for only one customer by distinguishing male and female clothes according to the explanation or desire. The weakness of Sharia Laundry is that launderers and owners dispose of laundry liquid waste in flowing water (ditch) which contains phosphates (toxic substances), thereby polluting surroundings and harming aquatic creatures, and they do not yield more particular discounts for mosque worship equipment as charity.